The Evolving Role of Technology in Public Administration: Challenges and Opportunities - Krhipa Pakhrim (Journal of Public Representative and Society Provision, 2026)
This looks at investigates the dynamics of technology integration inside public administration, focusing on the function of technological readiness, organizational subculture, and management support. Through a comprehensive analysis of survey records gathered from authorities’ employees, the have a look at examines the relationships among those key factors and the level of technology integration in authorities’ agencies. Descriptive records, correlational analyses, and regression models are hired to research the statistics and draw insights into the determinants of era adoption and usage. The findings underscore the important importance of fostering technological readiness, cultivating supportive organizational cultures, and making sure robust management dedication to pressure a success era integration initiative. Additionally, the examine highlights the need for targeted interventions tailor-made to the numerous needs and demanding situations confronted by using exceptional segments of the general public quarter group of workers. Overall, the observe contributes to the developing frame of information on technology adoption in public management, presenting practical insights for policymakers and organizational leaders searching for to navigate the complexities of virtual transformation.